Insights into the improvement of alkaline hydrogen peroxide (AHP) pretreatment on the enzymatic hydrolysis of corn stover: Chemical and microstructural analyses. (October 2018) - Li, Junbao; Lu, Minsheng; Guo, Xiaomiao; Zhang, Haiyan; Li, Yaping; Han, Lujia
Graphical abstract: Highlights: Alkaline hydrogen peroxide (AHP) pretreatment enhances the enzymolysis effect. Chemical and microstructural changes of AHP-pretreated corn stover were analyzed. AHP pretreatment decreases the unproductive adsorption of enzymes onto lignin. AHP pretreatment increases the accessibility of cellulose to enzymes. Abstract: The alkaline hydrogen peroxide (AHP) pretreatment (0.5 g H2 O2 /g corn stover, 30 °C, 24 h) removed 91.53% of the initial lignin and 55.77% of the initial hemicellulose in corn stover and afforded a considerable glucose yield (88.34%) through enzymatic hydrolysis. A combination of chemical and microstructural analyses was used to illustrate the mechanism of the effect of AHP pretreatment on enzymatic hydrolysis. During pretreatment, H2 O2 -derived radicals effectively spread into and destroyed the cell wall of various parts (vascular bundle sheath, xylem vessels, tracheid, phloem, and parenchyma) of corn stover to remove most of the lignin, acetyl group, and partial hemicellulose. They destroyed the compact structure of the cellulose-hemicellulose-lignin network, increased the cellulase-accessible pore volume by 6 times, doubled the area of exposed cellulose, and decreased the unproductive adsorption of enzymes onto lignin. Combining all the effects, AHP pretreatment effectively improved the cellulose accessibility to enhance the subsequent enzymatic hydrolysis efficiency.